VLSI 2010 Annual Symposium Selected papers - Voros, Nikolaos.; Voros, Nikolaos.; Mukherjee, Amar.; Mukherjee, Amar.; Sklavos, Nicolas.; Sklavos, Nicolas.; Masselos, Konstantinos.; Masselos, Konstantinos.; Huebner, Michael.; Huebner, Michael. (Lecture Notes in Electrical Engineering, 2011)
This book intends to serve as a basis for presenting to young and experienced scientists the latest advances in VLSI technology and related areas, and how they can be effectively employed for the design of modern systems. All contributions to the book have been carefully written, focusing on the pedagogical aspect so as to become a relevant teaching material. Therefore, this book addresses in particular students, postgraduate programmers/engineers or anyone interested in learning about the state-of-the-art technology in: Architecture - Level Design Solutions Embedded System Design Emerging Devices and Nanocomputing Reconfigurable Systems The book attempts to encompass both theory and technology, and both theoretical and practical design aspects. The authors present the latest research results, ideas, developments, and applications in the above areas that directly influence and become influenced by VLSI circuits, systems and design methods to system level design and Systems-on-Chip. The book includes twenty chapters, divided in four parts. Part I, presents Architecture - Level Design Solutions and especially network-on-chip technologies, cryptographic hardware engineering, multi-core architectures and architectures beyond CMOS; Part II, entitled Embedded System Design, presents novel approaches for designing the next generation of embedded systems focusing on MPSoC and multi-core technologies; Part III is devoted to Emerging Devices and Nanocomputing and presents techniques for efficiently designing and simulating memory systems and converters with low power testing techniques, while it also provides the latest technology on digital microfluidic biochips; Finally, Part IV presents state-of-the-art technologies for Reconfigurable Systems based on FPGA technology and multi-grained reconfigurable hardware.